Personality and risk of adult asthma in a prospective cohort study - Loerbroks, Adrian; Li, Jian; Bosch, Jos A.; Herr, Raphael; Angerer, Peter (Journal of psychosomatic research, 2015)
Objective: Traits conceptualized according to the five-factor model of personality have been found to predict numerous health outcomes and may also be predictive of asthma. Prior longitudinal studies on personality and asthma remain however sparse, have been restricted to only two traits (i.e., neuroticism and extraversion), and yielded inconsistent results. We therefore aimed to examine the potential relationships of all five-factor personality traits with incident asthma. Methods: We combined the 2009 and 2011 data from the population-based German Socio-Economic Panel study for longitudinal analyses (n=12,202). Personality traits were measured by an established 15-item version of the Big Five Inventory. Asthma was measured by participant-reports of having ever received such a diagnosis by a physician. We estimated multivariable risk ratios (RRs) and corresponding 95% confidence intervals (CIs) of trait-specific scores (continuous or categorized by tertiles) and incident asthma by Poisson regression. Results: Neuroticism was the only trait which was predictive of asthma (RR for the z-score=1.17, 95% CI=1.02-1.34; RR for the highest versus the lowest tertile=1.59, 95% CI=1.12-2.25). Associations between personality traits and asthma risk did not differ by sex (p-values for interaction ≥0.07). There were no two-way interactions between personality traits when we tested all potential combinations (all p-values for interaction ≥0.20). Conclusion: The present study suggests that high levels of neuroticism may predispose adults to develop asthma. Future longitudinal studies are needed to confirm our findings and to shed light on the potential psychophysiological processes underlying the observed association.